Use of Short-term Circulatory Support as a Bridge in Pediatric Heart Transplantation - Canêo,Luiz Fernando (2015)
Background:Heart transplantation is considered the gold standard therapy for the advanced heart failure, but donor shortage, especially in pediatric patients, is the main limitation for this procedure, so most sick patients die while waiting for the procedure.Objective:To evaluate the use of short-term circulatory support as a bridge to transplantation in end-stage cardiomyopathy.Methods:Retrospective clinical study. Between January 2011 and December 2013, 40 patients with cardiomyopathy were admitted in our Pediatric Intensive Care Unit, with a mean age of 4.5 years. Twenty patients evolved during hospitalization with clinical deterioration and were classified as Intermacs 1 and 2. One patient died within 24 hours and 19 could be stabilized and were listed. They were divided into 2 groups: A, clinical support alone and B, implantation of short-term circulatory support as bridge to transplantation additionally to clinical therapy.Results:We used short-term mechanical circulatory support as a bridge to transplantation in 9. In group A (n=10), eight died waiting and 2 patients (20%) were transplanted, but none was discharged. In group B (n=9), 6 patients (66.7%) were transplanted and three were discharged.The mean support time was 21,8 days (6 to 984h). The mean transplant waiting list time was 33,8 days. Renal failure and sepsis were the main complication and causeof death in group A while neurologic complications were more prevalent en group B.Conclusion:Mechanical circulatory support increases survival on the pediatric heart transplantation waiting list in patients classified as Intermacs 1 and 2.